Ultrasound Guided Thoracic Paravertebral and Coeliac Plexus Block for Open Cholecystectomy in a Patient with Multiple Co-Morbidities : A Case Report - Yadav, Rupesh Kumar; Rayamajhi, Anuj Jung; Dhungel, Bidur Kumar; Poudel, Subash Chandra; Poudel, Prashanta; Pokhrel, Kapil; Pangeni, Anang; Byanjankar, Bikram (Birat Journal of Health Sciences, 2018)
Ultrasound guided nerve blocks are gaining popularity these days due to its higher accuracy and reduced incidence of complications. Ultrasound guided unilateral paravertebral block in combination with unilateral coeliac plexus block and unilateral Rectus sheath block in patients with multiple co-morbidities provides adequate anesthesia for surgery and it also reduces incidences of mortality, morbidity and hospital stay in comparison to General anesthesia and spinal / epidural anesthesia. Paravertebral block , Coeliac plexus block and Rectus sheath blocks can be performed with higher success rate with the use of ultrasound. BJHS 2018;3(2)6:508-510.